No 'Stinkefinger' and renal failure: do you see a link? - Zeier, Martin; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1999)
During the last World Soccer Championship, Stefan Effenberg, a member of the German team, was sent home because he had insulted the fans by raising an isolated middlefinger which is an obscene and insulting gesture with sexual implications. The following case shows that on the other hand a close watch for the middlefinger may be of help to the nephrologist and enable him occasionally to arrive at the correct diagnosis.A patient born in 1961 was admitted whose mother had no renal disease and whose father was unknown. He had persistent proteinuria and intermittent microhaematuria from age 15 years onward. This had prompted urological examination which showed upon intravenous urography deformed calyces, deep scars (more pronounced of the left than the right kidney) and absence of vesicoureteral reflux by cystoscopy. At 30 years of age he was known to be hypertensive and transiently took beta blockers. At 35 years of age his blood pressure had risen to values of permanently above 150/100 mmHg. At 37 years of age he presented with a serum-creatinine of 1.87 mg/dl and proteinuria of 5 g/l. Inspection showed malformation of the hands with bilateral absence of the middle finger (Figure 1). The feet were also malformed (Figure 2). As a potentially incidental finding, he had an accessory mammilla.